2020
DOI: 10.2147/ccide.s247179
|View full text |Cite
|
Sign up to set email alerts
|

<p>Dental Caries and Associated Factors Among Patients Attending the University of Gondar Comprehensive Hospital Dental Clinic, North West Ethiopia: A Hospital-Based Cross-Sectional Study</p>

Abstract: Purpose: Dental caries are an emerging public health problem in developing countries in the last two decades. However, there is a paucity of data on dental caries in northwest Ethiopia. This study investigated the prevalence of dental caries and associated factors in northwest Ethiopia. Patients and Methods: A hospital-based cross-sectional study was conducted in 368 patients who visited the University of Gondar Comprehensive Hospital Dental Clinic. A systematic random sampling technique was used to select the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
6
16
0
Order By: Relevance
“…Many studies revealed that the magnitude of dental caries vary in different countries like Northwest of Spain (36.9%), Nigeria (13.9%), Kenya (50.3%), and Eritrea (78%) respectively [9][10][11][12]. Studies that have been conducted in Ethiopia revealed that dental caries accounts for about 21.1-78.2% [13][14][15][16][17][18][19][20][21][22][23][24][25]. Although scholars recommended modification of free sugar consumption, cleaning teeth more than two times a day using a fluoride toothpaste (promotion of good oral hygiene), and oral health education, the problem remains high, particularly in developing countries [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies revealed that the magnitude of dental caries vary in different countries like Northwest of Spain (36.9%), Nigeria (13.9%), Kenya (50.3%), and Eritrea (78%) respectively [9][10][11][12]. Studies that have been conducted in Ethiopia revealed that dental caries accounts for about 21.1-78.2% [13][14][15][16][17][18][19][20][21][22][23][24][25]. Although scholars recommended modification of free sugar consumption, cleaning teeth more than two times a day using a fluoride toothpaste (promotion of good oral hygiene), and oral health education, the problem remains high, particularly in developing countries [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…7,25,26 Similarly, a study from the University of Gondar, Debre Tabor, and Addis Ababa indicated the statistical association between tooth cleaning and poor dental hygiene with dental caries. 5,6,10 Moreover, individuals with gastritis had more chance of developing dental health problems. As presented in the multivariable analysis, the risk of developing dental health problems increased by threefold when individuals had gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Two-sided confidence level (95%), power (80%), the ratio of controls to cases (1:1), percentage of controls exposed (77.6%), Odds Ratio (OR = 0.42) for teeth brushing practice, and percentage of cases with exposure (59.3%). 5 Thus, 111 cases and 111 controls were taken to make the total sample size 222. Finally, adding 20% of the non-response rate, the total study participants calculated was 267.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations